Multiple pathogen infections accompanied with ocular pathologies in a patient with high-titer Anti-IFN-γ autoantibodies: a case report - Siyao Wu; Siqiao Liang; Hanlin Liang; Yan Ning; Xia Li; Zhiyi He (BMC Infectious Diseases)
Abstract The typical clinical characteristic of patients with anti-IFN-γ autoantibodies (AIGAs) is primarily associated with infection caused by intracellular pathogens. With continued research, additional clinical characteristics have been gradually uncovered. Here, we present a case of multiple pathogen infections accompanied by ocular pathologies in a patient with high titers of AIGAs. The patient, a 53-year-old female patient, was admitted to our hospital after finding a mass in the right supraclavicular fossa. She was successively diagnosed with Talaromyces marneffei, Aspergillus flavus and Nontuberculous mycobacteria (NTM) infections. Then, she received a complete course of antifungal agents for nearly 3.5 years and anti-NTM treatment for nearly 3 years, with discontinuation upon symptom improvement. However, there was a rapid recurrence of the infection upon cessation of the drug despite improvement in the patient’s symptoms. Moreover, when the recurrent infection stabilized, the patient exhibited immune conjunctivitis and dry eye, which was successfully treated by tacrolimus eye drops and lubricant. Patients with high-titer AIGAs are more prone to experiencing recurrence and/or persistent infection, as well as immune disorders.